Indicadores morfométricos: uma ferramenta no diagnóstico da vulnerabilidade ambiental - Costa, Renata Cristina Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study attempts to propose environmental indicators of public poli-cies from the spatial distribution of morphometric characteristics and its relation to areas in environmental conflict and vulnerability of environmental deterioration. As a result of this analysis hydrological compartments were considered as evaluation units, and in them were determined the morphometric parameters as: area, perime-ter, length of the drainage network, drainage density, number of channels, frequency of rivers and relief to evaluate the natural erosion, using the land use conflict tech-nique and the vulnerability of the watershed. The morphometric parameters were submitted to descriptive and exploratory multivariate statistical analysis. The autocor-relation between the morphometric parameters and the similarity between the hydro-logical compartments were evaluated. The spatial distribution of the values of the number of channels (Nt) has generated environmental physical indicators which enbled the areas of differentiation. Identifying the use of conflict zones is as important tool to propose plans of management and conservation of land use, aiding in the making of public officials decision. The vulnerability map of the watershed for the multicriteria analysis (MCA) indicated morphometric standards of the most vulnerable areas to natural soil erosion and consequently greater environmental fragility. The high correlation between the vulnerability of the basin validates the theory of the risk of erosion and environmental deterioration and can be used as a tool and environ-mental vulnerability indicator in watersheds. The environmental evaluation of Jabuti-cabal watershed indicated that the watershed has low impact and of little signifi-cance, but the degree of average of the real deterioration determined by the matrix by Leopold-Rocha shows that the environment is deteriorated, since the obtained value is above the acceptable rate and should be ...

Este trabalho busca propor indicadores ambientais de políticas públicas a partir da espacialização das características morfométricas e sua relação com áreas em conflito e vulnerabilidade da deterioração ambiental. Como resultado dessa aná-lise as bacias hidrigráficas foram consideradas como unidades de avaliação e foram determinados os parâmetros morfoméricos de área, perímetro, comprimento da rede de drenagem, densidade de drenagem, número de canais, frequência de rios e rele-vo para demonstar os padrões de erosão natural, utilizando a técnica de conflito de uso do solo e de vulnerabilidade da bacia hidrográfica. Os parâmetros morfométricos foram submetidos à análise estatística descritiva e exploratória multivariada, sendo possível determinar a autocorrelação entre estes e a similaridade das bacias. A es-pacialização dos valores obtidos do número de canais (Nt) gerou indicadores físicos ambientais que possibilitaram a diferenciação de áreas. A identificação das zonas de conflito de uso é uma ferramenta importante para propor planos de manejo e con-servação do uso do solo, auxiliando na tomada de decisão de agentes públicos. O mapa de vulnerabilidade obtido da análise multicritério (MCA) indicou os padrões morfométricos das áreas mais vulneráveis ao processo erosivo natural do solo e consequentemente maior fragilidade ambiental. A alta correlação entre a vulnerabili-dade das áreas valida à teoria do risco de erosão e deterioração ambiental, podendo ser utilizada como ferramenta e indicador da vulnerabilidade ambiental em bacias hidrográficas. A avaliação ambiental da microbacia do Jabuticabal indicou que a área apresenta pequeno impacto e de pouca significância, porém o grau de deterio-ração real médio determinado pela matriz Leopold-Rocha mostra que o ambiente encontra-se deteriorado, uma vez que o valor encontrado está acima da...
Keywords: Bacias hidrograficas; Solo - Uso; Impacto ambiental; Morfometria; Indicadores ambientais; Environmental impact statements